2011
DOI: 10.1111/j.1556-4029.2010.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Accidental Hanging by a High‐chair Waist Strap in a 2‐Year‐old Girl

Abstract: High chairs are commonly used to feed children after 6 months. Related injuries are oftentime minor and rarely leading to death. We describe a case of a 2-year-old female child who used to jump alone on her high chair and also had the habit to fasten the straps by herself. Her mother found her hanging by the waist straps. A thorough investigation showed that she climbed her high chair and fastened the waist straps but not the crotch one. The girl slid down into the seat, trapping her neck in the waist straps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…22 In a recent incident, a young child died when her neck was entrapped in the improperly fastened waist restraint of her high chair. 23 Because chairs are not equipped with the safety restraint systems, children can more easily assume unsafe positions on chairs. Therefore, it is important for caregivers to discourage standing and climbing behaviors as children are transitioned from high chairs into chairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In a recent incident, a young child died when her neck was entrapped in the improperly fastened waist restraint of her high chair. 23 Because chairs are not equipped with the safety restraint systems, children can more easily assume unsafe positions on chairs. Therefore, it is important for caregivers to discourage standing and climbing behaviors as children are transitioned from high chairs into chairs.…”
Section: Discussionmentioning
confidence: 99%
“…23 Because chairs are not equipped with the safety restraint systems, children can more easily assume unsafe positions on chairs. Therefore, it is important for caregivers to discourage standing and climbing behaviors as children are transitioned from high chairs into chairs.…”
mentioning
confidence: 99%
“…10 The authors have reported cases of near-hanging by a window blind cord and high chair waist strap in the hope of heightening awareness of these potentially fatal injuries among community practitioners. 11,12 The mode of injury in our case was unique and it has not been reported previously. The ropes of a cot kept upright caused this ligature.…”
Section: Discussionmentioning
confidence: 57%
“…Cases were reported with scarf wrapped around swinglike cradles [9]. Out of the sleeping environment, hanging can occur when children will wrap around their necks curtain cords or electric flexes [4,10] or when they slip down in high-chair or restraining seats and will hang on the waist strap [11]. Cases of hanging due to head entrapment were also reported [12,13] and of accident in playgrounds [14].…”
Section: Discussionmentioning
confidence: 99%